2003
DOI: 10.1038/sj.bjc.6601217
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of docetaxel and cisplatin with concurrent thoracic radiation therapy for locally advanced non-small-cell lung cancer

Abstract: Recent studies have suggested the superiority of concomitant over sequential administration of chemotherapy and radiotherapy. Docetaxel and cisplatin have demonstrated efficacy in advanced non-small-cell lung cancer (NSCLC). This study evaluated the safety, toxicity, and antitumour activity of docetaxel/cisplatin with concurrent thoracic radiotherapy for patients with locally advanced NSCLC. Patients with locally advanced NSCLC (stage IIIA or IIIB), good performance status, age p75 years, and adequate organ fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 36 publications
1
37
1
Order By: Relevance
“…In several recent reports, preoperative chemoradiotherapy in patients with LA-NSCLC was shown to be feasible and effective, although the new drugs developed in the 1990s such as irinotecan and docetaxel were not included (Albain et al, 1995;Choi et al, 1997;Eberhardt et al, 1998;Thomas et al, 1999). We have already confirmed the feasibility and effectiveness of concurrent chemoradiotherapy using cisplatin and docetaxel in patients with unresectable LA-NSCLC (Kiura et al, 2003), whereas a combination of cisplatin, irinotecan and concurrent thoracic irradiation has been reported to be toxic and unacceptable (Yokoyama et al, 1996). Based on these results, the present study was planned to assess the feasibility and effectiveness of this chemoradiotherapy as preoperative treatment in patients with LA-NSCLC.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…In several recent reports, preoperative chemoradiotherapy in patients with LA-NSCLC was shown to be feasible and effective, although the new drugs developed in the 1990s such as irinotecan and docetaxel were not included (Albain et al, 1995;Choi et al, 1997;Eberhardt et al, 1998;Thomas et al, 1999). We have already confirmed the feasibility and effectiveness of concurrent chemoradiotherapy using cisplatin and docetaxel in patients with unresectable LA-NSCLC (Kiura et al, 2003), whereas a combination of cisplatin, irinotecan and concurrent thoracic irradiation has been reported to be toxic and unacceptable (Yokoyama et al, 1996). Based on these results, the present study was planned to assess the feasibility and effectiveness of this chemoradiotherapy as preoperative treatment in patients with LA-NSCLC.…”
mentioning
confidence: 53%
“…We thus considered that cisplatin plus docetaxel would be an excellent regimen to incorporate in concurrent chemoradiotherapy for LA-NSCLC. We previously reported that combined modality therapy using cisplatin and docetaxel with concurrent thoracic irradiation was feasible and effective in patients with unresectable LA-NSCLC (Kiura et al, 2003). The regimen achieved good control of local tumour and also of distant metastases.…”
Section: Discussionmentioning
confidence: 98%
“…However, for many of these newer agents, the dose-limiting toxicities require that lower doses be given during the concurrent phase (Choy et al, 1998;Vokes et al, 2002;Kiura et al, 2003;Belani et al, 2005;Fournel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the findings of Maguire et al [8] , we did not find any significant association between the incidence of esophagitis and the the longitudinal and circumferential characteristics of the esophagus. However, Kiura et al [12] , reported that concurrent thoracic radiation therapy and chemotherapy are effective and tolerable in patients with advanced NSCLC. Singh et al [13] , found that concurrent chemotherapy is significantly associated with the risk of grade 3-5 esophageal injury in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%